DISCURSIVE PRACTICES OF EDUCATION AND CHANGE OF PARADIGM - Natalya I. Martishina (Высшее образование в России)
The report is a response to the article by A.A. Polonnikov «Situational description and discursive responsibility». The author argues that the idea of a fundamental upgrade of discursive practices of education is an indicator of a special phase in the development of education, defined as a paradigm shift, and gives her own opinion on the possibilities and limits of the use of the discourse as a tool to change the paradigm.